Comparison of Monopoly and Sharing Line-haul Vehicles in Express Delivery Service - Friska Natalia Ferdinand (Universitas Multimedia Nusantara, 2015)
In the Korean express delivery service market, many companies have been striving to extend their own market share and interested in collaboration through sharing resources such as line-haul vehicles and service centers. Collaboration has recently attracted a great deal of attention as an effective way to secure competitive advantage for companies with limited resources. Some companies operate line-haul vehicles in milk-run types of pick-up and delivery services among consolidation terminals and service centers with locational disadvantages so they can represent as traditional pick-up and delivery problem (PDP). This study proposes the design of express delivery service networks operate only one service center shared by different companies for service centers with low demands by comparing two systems: (i) Monopoly of line-haul vehicles and (ii) Sharing of line-haul vehicles Keywords: Express Delivery Service, COllaborative Network Design, Comparison, Monopoly, Sharing